Infrared spectroscopic studies on the dipalmitoyl phosphatidylcholine bilayer interactions with calcium phosphate: Effect of vitamin D2. Issue 3 (2002) - Toyran Toyran, Neslihan Neslihan; Severcan Severcan, Feride Feride
Abstract : In the present work, the interaction of calcium-phosphate with DPPC (dipalmitoyl phosphatidylcholine) model membranes has been studied in the presence and absence of vitamin D2 by using Fourier Transform Infrared (FTIR) spectroscopy. Calcium and phosphorus are the most abundant elements in the body. They combine in the form of calcium phosphate salt, called hydroxyapatite. Hydroxyapatite is the major structural component of the bone. Calcium phosphate assists with the digestion and absorption of food and is vitally important for the building of sturdy bone and body structures and a robust constitution. Phosphorus is extracted from foods and its use is controlled by vitamin D and calcium. FTIR spectral analysis results suggested that, calcium–phosphate complex, which is the major component of the bones, decreases the phase transition temperature to lower values, causes a loss in cooperativity of the acyl chains, decreases the order of the membrane in both phases and decreases the dynamics of the membrane in the liquid crystalline phase, increases the flexibility of the chains in the center of the bilayer in both phases, and increases the mobility of the head group of DPPC in the gel phase. The effect of calcium‒phosphate on DPPC liposomes diminishes with the addition of vitamin D2 into the liposomes. Our results suggest how calcium‒phosphate and/or vitamin D2, which have indispensable role for the functioning of the bone tissue, affect the thermal behaviour of DPPC liposomes at molecular level.